Small Bowel Perforation due to Gossypiboma Caused Acute Abdomen - Tahsin Colak; Tolga Olmez; Ozgur Turkmenoglu; Ahmet Dag (Case Reports in Surgery)
Gossypiboma, an infrequent surgical complication, is a mass lesion due to a retained surgical sponge surrounded by foreign body reaction. In this case report, we describe gossypiboma in the abdominal cavity which was detected 14 months after the hysterectomy due to acute abdominal pain. Gossypiboma was diagnosed by computed tomography (CT). The CT findings were a rounded mass with a dense central part and an enhancing wall. In explorative laparotomy, small bowel loops were seen to be perforated due to inflammation of long standing gossypiboma. Jejunal resection with end-to-end anastomosis was performed. The patient was discharged whithout complication. This case was presented to point to retained foreign body (RFB) complications and we believed that the possibility of a retained foreign body should be considered in the differential diagnosis of who had previous surgery and complained of pain, infection, or palpable mass.